Credit risk modelling : a hybrid approach using KMV-merton and CreditRisk+. - Cheng, Ming Kang. (2010)
This paper focuses on the use of a combination of a structural model (KMV-Merton) and a reduced-form model (CreditRisk+) to generate a loss distribution of a loan portfolio. We will provide a brief literature review and mathematical derivation of the two models. Next we will apply the KMV-Merton Model to a group of companies from the Singapore Exchange (SGX) to obtain the Merton Expected Default Probability for each company. We will then use these results as the parameters in the implementation of the CreditRisk+ Model for the calculation of the loss distribution of a loan portfolio.